Supply-chain survival in the age of globalization - Pope, James A. (James Arthur), 1950- (Supply and operations management collection, 2012)
When supply-chain management moves into the global arena the problems are profoundly different from those in domestic supply chains. This book will examine the history and background of global supply chains, some of the unique problems faced when managing a global supply chain, and some ways of dealing with these problems. Each chapter ends with suggested action items for the global supply-chain manager.